PP35 Evaluation of a rotational model of advanced paramedic practice in north wales: a logic model approach to demonstrate effectiveness. Issue 10 (25th September 2020) - Robertson, Duncan; Baines, Bob; Nosworthy, Gemma; Thomas, Wyn; Timmins, Mark; Watson, Robyn; Wright, Stella
Abstract : Background: UK Ambulance Services are under pressure to retain paramedics as diverse career options become increasingly available throughout the NHS for this valuable group of staff. Rotational working is one means of providing a varied clinical portfolio with the aim of sustaining an ambulance service based career over a longer work-span. Prior to implementing a test of an Advanced Paramedic Practitioner (APP) focussed three-part model of rotation which included Primary Care, Clinical Contact Centre and Solo Responding, an effective evaluation framework was required. Methods: The aims of the project were refined during initial team planning and a project workshop which articulated the conditions for success. The theory of change was subsequently developed through a team-based facilitated session culminating in the development of a driver diagram. Due to the predominantly linear nature of the project and design, a Logic Model approach was selected to then map and construct the detailed evaluations required for each of the key areas identified. Results: Seven individual elements for evaluation were identified through this design process. These comprised of four core areas including the impact of the rotation on Patients, Primary Care, The APPs and Welsh Ambulance Services NHS Trust which would be managed by the project team. In addition, the framework identified elements suitable for external evaluation which consisted of the economic evaluation, a deeper exploration of patient experiences and project effectiveness. External evaluation would test the validity of the overall approach to the project by the internal team and stakeholders. The derived Logic Models were designed to enable formative and summative evaluation throughout the opening phase of the rotation. Conclusions: Using this approach, the project team have constructed a robust, but testable model of evaluation, with the flexibility to map changes as the evaluation yields specific learning points about the project.